Hall‐effect sensors based on AlGaN/GaN heterojunctions on Si substrates for a wide temperature range - Sagnik Kumar; R. Muralidharan; G. Narayanan (IET Circuits, Devices and Systems)
Abstract The authors report experimental investigations on Hall sensors based on AlGaN/GaN heterojunctions grown on silicon 111 (Si 111) substrates. Realisation of two‐dimensional electron gas‐based Hall sensors on Si substrates can have the advantages of low cost and integrability with complementary metal‐oxide semiconductor circuits. Design and fabrication of such Hall sensors and their characterisation over a wide temperature range of 75 to 500 K are reported. The authors experimentally investigate the temperature dependence of the transresistances, sheet resistance and current‐related sensitivity (or gain) of such Hall sensors. The current‐related sensitivity is shown to be reasonably constant over the complete temperature range and certain inevitable variations in current‐related sensitivity can easily be compensated. The temperature dependence of the transresistance can be used for such compensation. The variation of the geometrical correction factor of the Hall sensor with the applied magnetic field strength and the operating temperature is also studied. The authors also demonstrate the possibility of realising Hall sensors with a high geometrical correction factor ( ≈0.97), which is practically insensitive to variations in temperature ( ≃2% from 75 to 500 K) and applied magnetic field, for applications such as in electromechanical devices.